A TRANSITIVITY ANALYSIS OF THE NOVEL "GONE WITH THE WIND" BY MARGARET MITCHELL / Trần Thị Lan Hương; NHDKH Đỗ Kim Phương, Ph.D - Trần, Thị Lan Hương
This study is concerned with Transitivity System used Chapter 2 of the novel "Gone with the Wind" by Margaret Mitchell. The purposes of this research are to identify the process types of transitivity system, to find out their significance in the characterisation of each character in Chapter 2 as well as to describe the implications of the analysis. This study is conducted by applying descriptive, analytic and statistical methods. There are 395 clauses selected from the chapter . All the process types of transitivity system are found in Chapter 2, which are material, mental, relational, behavioral, verbal and existential process. The result of the analysis is shown as follows : material (42,53%), mental (19,75%), relational (28,86%), verbal (5,82%), behavioral (0,76%), and existential (2,28%). In addition, the result also presents the occurrences of process types with each of the five characters in the chapter. This is carefully discussed in Chapter 4 of the study. The findings of the study can, to some extent, be used as some suggestions for English teachers and learners to have more access to Process types of Transitivity System in order to achieve success in teaching and learning writing English texts. Besides, linguistics researchers of Systemic Functional Grammar can conduct further study on the similar topics to investigate another aspects of the issue.